Exploring B40 and M40 households’ satisfaction on loan moratorium during pandemic era - Hor, Ching Yee; Ng, Siao Sin; Periyja, Kalaichelven; Swetha Sen, Suresh; Wong, Min Jeah (2021)
Most of the individuals in Malaysia are currently face a financial difficulty due to Covid-19 cases risen tremendously. This has become a major issue for all Malaysians especially the B40 and M40 households’ where Malaysia government implemented Movement Control Order (MCO) as a preventive measure against covid-19 and has led all industries to closed except for certain sectors. As a solution, BNM has implemented a loan moratorium for the Malaysians especially to targeted group households’ such as B40 and M40. However, there are some implications to B40 and M40 which have not yet fully been realized through the studies and investigations done. Therefore, this experiment attempts to explore the factors effects on the satisfaction level among B40 and M40 toward the loan moratorium implemented by BNM during the COVID-19 pandemic. This study takes into account of knowledge loan moratorium and four factors that affect the satisfaction level namely financial literacy, saving pattern, purchasing power and stress level that address the concern of B40 and M40 households. Primary data is collected for this research by delivering self-administered questionnaire to a sample of 400 respondents who are 21 years old and above in Selangor, Malaysia. The demographic profile of target respondents has been analyzed in this study. Besides, the reliability and normality test, inferential analysis through Pearson Correlation test and Multiple Linear Regression analysis will be conducted to analyze the data collected from target respondents. Furthermore, this paper links the Kano model with measuring customer satisfaction and presents a contribution for marketing research theory. Therefore, the results could be used to support optimization of business decision-making, as well as for further scientific research. This research attempts to contribute to bank analysts, future researchers, and the government to have better understanding of consumer satisfaction level toward loan moratorium in Malaysia. Besides that, they can do some improvements to the loan moratorium to increase the satisfaction level of both B40 and M40.